God's Foolishness : Poems - Wenthe, William, 1957- (Book collections on Project MUSE., 2016)
St. Paul writes "the foolishness of God is wiser than men." The poems in William Wenthe's God's Foolishness mine the feelings of human uncertainty in matters of love and desire, time and death, and uncover difficult truths with transformative insights. These are poems of crisis. Wenthe examines our conflicting urges to see nature as sustenance and to foolishly destroy it. His poems shift from close observation to panorama with cinematic fluidity, from a tea mug to an ancient monument, from a warbler on an elm branch to the specter of imminent natural disaster. Offering passion and intellect balanced with a careful concern for poetic craft, Wenthe's God's Foolishness gives us fine poems to savor and admire.